Treatment of femoral and tibial fractures in puppies by elastic plate osteosynthesis - Sarrau, S.; Meige, F.; Autefage, A. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Seventeen puppies, two to four months old, with a femoral (n=12) or tibial (n=5) diaphyseal fracture were treated by elastic plate osteosynthesis with a Veterinary Cuttable Plate (VCP) or straight plate. In one case of femoral fracture treated with a VCP, plate bending due to an excessive elasticity of the implant was observed three days after the osteosynthesis and surgical revision was required. Two cases of femoral overgrowth and one case of slight femoral head and neck retroversion were identified during the radiographic follow-up but without any clinical consequences. Bone healing was obtained for all fractures four to eight weeks (5.64±0.88 weeks) after the surgical procedure, and functional results were excellent in all cases. Our study confirms that elastic plate osteosynthesis with either a VCP or straight plate can be used to treat femoral diaphyseal fractures in medium and large breed puppies less than four months old, but that modification of implant elasticity or rigid osteosynthesis use is required when such puppies reach four months. The same technique can also be used successfully to treat tibial fractures in puppies younger than four months old.
Keywords: Puppy; fracture; femur; tibia; osteosynthesis